The occurrence of leucism in groups of tayras Eira barbara linnaeus 1758 on the Guyana shield - Pontes, Antonio Rossano Mendes; Silva, Antonio Paulo da; Chivers, David John (Ecoscience, 2020)
We report leucism in groups of up to five tayras, Eira barbara, in a fish-bone human settlement in southern Roraima, centre of the Guyana shield of the Brazilian Amazonia, during systematic line transect surveys in Terra Firme forests. These tayras had much larger non-rounded ears, and much larger and robust paws compared to current descriptions of the species. The leucistic individuals were snow-white with the exception of the distal half of the forearms, front paws, and the eyes, which were black. Leucism appeared to be commoner in this region than in the rest of the Guyana shield, as it occurred in a non-isolated population. The leucistic individuals did not appear to face the disadvantages reported in the literature, such as competitive exclusion, or difficulties in intra-specific communication and recognition. © 2020 Universite Laval. All rights reserved.
Keywords: Human Settlement; Line Transect; Literature Review; Morphology; Transect; Amazonia; Brazil; Guyana Shield; Roraima; Eira Barbara